Efficacy of water‐only or soap and water skin decontamination of chemical warfare agents or simulants using in vitro human models: A systematic review. Issue 6 (19th October 2021) - Chiang, Chavy; Kashetsky, Nadia; Feschuk, Aileen; Burli, Anuk; Law, Rebecca M.; Maibach, Howard I.
Abstract: Water‐only or water and soap are widely recommended as preferred solutions for dermal decontamination. However, limited efficacy data exist. We summarized experimental studies evaluating in vitro efficacy of water‐only or soap and water in decontaminating chemical warfare agents (CWA) or their simulants from human skin models. Embase, Covidence®, MEDLINE, PubMed, Web of Science, and Google Scholar were searched for articles using water‐only or soap and water decontamination methods for removal of CWA/CWA simulants in in vitro human skin models. Data extraction was completed from seven studies, yielding seven contaminants. Water‐only decontamination led to partial decontamination in all skin samples (100%, n  = 81/81). Soap and water decontamination led to partial decontamination in all skin samples (100%, n  = 143/143). Four studies found decontamination to either paradoxically enhance absorption of contaminants or their penetration rates, known as the "wash‐in" effect. Despite recommendations, water‐only or water and soap decontamination were found to yield partial decontamination of CWA or their simulants in all human in vitro studies. Thus, more effective decontaminating agents are needed. Some studies demonstrated increased or faster penetration of chemicals following decontamination, which could prove deadly for agents such as VX, although these findings require in vivo validation. Heterogeneity in experimental setups limits interstudy comparison, and it remains unclear when water‐only or water and soap are ideal decontaminants, which requires more studies. Pending manuscripts will summarize in vivo human and animal efficacy data. International harmonized efficacy protocol should enable more efficient public health decisions for evidence‐based public health decisions. Abstract : Water‐only or water and soap are widely recommended as preferred solutions for dermal decontamination. However, limited efficacy data exist, and they demonstrate water‐only or water and soap decontamination to yield partial decontamination of chemical warfare agents.